Sustainable Tourism Development Strategy Through the Implementation of the Community-Based Tourism in the South Rayon of Donorojo, Pacitan - Gustaman, Fulia Aji; Mustofa , Moh. Solehatul; Rini , Hartati Sulistyo; Wardana , Ardiansyah Putra (Komunitas: International Journal of Indonesian Society and Culture, 2024)
The purpose of this study is to analyze the concept of CBT in the development of local tourism in the southern Rayon area of ​​Pacitan related to the natural environment and socio-cultural economy as a strategy to develop a sustainable tourism framework. This study emphasizes a descriptive qualitative research approach that provides an overview of how the involvement of village communities in tourism development in the southern coastal area. The data collection methods used in this study are observation, in-depth interviews, and documentation. Observations were carried out in several related tourism areas such as tourist areas in the Kalak Village, Sendang Village, Widoro Village, and Sawahan Village areas. Research informants in this study involved several related parties such as business actors in the area around the tourist area, members of the Pokdarwis group, local village officials, and several residents in the related tourist area. The results of this study indicate that community involvement in the context of CBT can be seen in two main thing, namely the environment aspect and the socio-cultural economy aspect. In terms of the environment, CBT is seen in the strengthening of tourism infrastructure such as stalls, souvenir shops, car and motorbike parking, toilets, homestays, road access, fishing area and others. Meanwhile, in the socio-cultural economic aspect, CBT appears in the role of local community institutions such as BUMDes and Pokdarwis which act as a bridge to mediate the role of the community to be involved in the tourism development process in rural areas.